2013
DOI: 10.1103/physrevb.87.245127
|View full text |Cite
|
Sign up to set email alerts
|

Topological insulators in transition-metal intercalated graphene: The role ofdelectrons in significantly increasing the spin-orbit gap

Abstract: We study the effect of transition metal intercalation of graphene on the formation of twodimensional topological insulator with experimentally measurable edge states. Our first-principles calculations reveal that the spin-orbit coupling (SOC) gap in Re-intercalated graphene on SiC(0001) substrate can be as large as 100 meV. This value is five orders of magnitude larger than that of pristine graphene. Similar effect should also exist in Mn-or Tc-intercalated graphene. A tight-binding model Hamiltonian analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…In accordance with a number of works [17][18][19] a QSH phase in graphene was predicted to be formed due to deposition of certain heavy adatoms on graphene induced by enhanced SO coupling strength. Moreover, it has been predicted that the topological phase can be developed in transition metals (Re [19] and Mn [40]) intercalated graphene with formation of the increased SO gap due to orbital coupling between the graphene π states and transition metal d states.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In accordance with a number of works [17][18][19] a QSH phase in graphene was predicted to be formed due to deposition of certain heavy adatoms on graphene induced by enhanced SO coupling strength. Moreover, it has been predicted that the topological phase can be developed in transition metals (Re [19] and Mn [40]) intercalated graphene with formation of the increased SO gap due to orbital coupling between the graphene π states and transition metal d states.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, it has been predicted that the topological phase can be developed in transition metals (Re [19] and Mn [40]) intercalated graphene with formation of the increased SO gap due to orbital coupling between the graphene π states and transition metal d states. For the Pbintercalated graphene on Ir(111) [21] the most important factor for formation of the topological phase (and corresponding generation of a pseudomagnetic field resulting in the formation of Landau-like levels) was a spatial gradient of SOI along the surface formed by a c(4 × 2) superstructure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of a spin-orbit gap in graphene is intensively discussed, for instance, under the influence of heavy impurity atoms on graphene [43] or for transition-metal intercalated graphene [44]. It was shown that hybridization of the d states of heavy atoms with the π states can lead to a topological spin-orbit gap in the electronic structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent proposals to induce a topological phase in graphene include functionalization with heavy adatoms [29,268], covalent functionalization of the edges [269], proximity effect with other topological insulators [270,271,272], or intercalation and functionalization with 5d transition metals [273,274]. In particular, the seminal theoretical study [29] by Weeks and co-workers has revealed that graphene endowed with modest coverage of heavy adatoms (such as indium and thallium) could exhibit a substantial band gap and QSHE fingerprints (detectable in transport or spectroscopic measurements).…”
Section: Introductionmentioning
confidence: 99%